School-Related Gender Based Violence (SRGBV) in Lebanon - Mansour, Ziad; Karam, Suha (Beirut La Sagesse University /UNESCO / Government of Italy, 2012)
The cultural norms and the patriarchal society in Lebanon contribute to encouraging discrimination and any form of violence against women and children.
(3GdfhY (B: Reports
Keywords: Gender; Sexe Violence; Violence; (3GdLfOQ GdYfas